Середовищезнавство - перспективний розділ науки - Голубець, М.А. (№8, 2007)
The necessity of environment study formation as applied to geosociosystemology branch of knowledge is substantiated, its object is ambient to a human being eco logical, social and economic (geosociosystem) environment, and its subject is its ecological, social and economic parameters, their complex special and time changes, modeling, forecast of changes and substantiation of control methods over these changes.